2007
DOI: 10.1097/01.ncn.0000270040.14541.37
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Women's Evaluations of an Audio/Video Computer-Assisted Perinatal Violence Screen

Abstract: For universal screening to become a reality, research must first validate the effectiveness and acceptability of violence screening. This study describes postpartum women's perceptions of an anonymous computer-assisted self-interview for perinatal violence screening. A sample of 519 postpartum women completed interviews that included audio and video enhancements. Post-response evaluations were positive with most women, indicating that they preferred computer interviews to face-to-face or written abuse screenin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…In addition, for the vast majority of women who were using a computer for the first time, it may not have been as clear how ACASI data would be stored, analyzed, and interpreted in comparison with information disclosed in FTFI. Indeed, other studies on domestic violence have shown that ACASI may not be the optimal mode of data collection (Renker & Tonkin, 2007) or necessarily superior to FTFI (Kim et al, 2008; MacMillan et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, for the vast majority of women who were using a computer for the first time, it may not have been as clear how ACASI data would be stored, analyzed, and interpreted in comparison with information disclosed in FTFI. Indeed, other studies on domestic violence have shown that ACASI may not be the optimal mode of data collection (Renker & Tonkin, 2007) or necessarily superior to FTFI (Kim et al, 2008; MacMillan et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…This question is beyond the scope of our study but should be addressed by future research. Aside from the research usefulness of ACASI, because studies have suggested that participants may report more honestly with ACASI (Hewett et al, 2003;Renker & Tonkin, 2007;Turner et al, 1996), it could be quite useful clinically, especially in detention settings where risk profiles are typically high. The rate of reported physical abuse (25.7%) and sexual abuse (11.4%) in our study is outside the range of estimates for physical abuse (57-81%) (Acoca & Dedel, 1998;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Ryder, 2007;Simkins et al, 2004) and sexual abuse (25-67%) (Abrantes, Hoffman, & Anton, 2005;Acoca & Dedel, 1998;Alemagno et al, 2006;Belknap & Holsinger, 2006;Chamberlain & Moore, 2002;Dembo, Williams, & Schmeidler, 1993;Goodkind, Ruffolo, Bybee, & Sarri, 2009;Gover, 2004;Lederman et al, 2004;Ruffolo, Sarri, & Goodkind, 2004;Simkins et al, 2004) reported by justiceinvolved girls.…”
Section: Refusalsmentioning
confidence: 99%
“…Murphy et al, 2000) and those with histories of domestic violence (e.g. Renker & Tonkin, 2007). While ACASI has been used in diverse settings and with various topics, there have been relatively few studies that have used ACASI to assess child maltreatment (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Computer-based psychosocial assessment conducted in primary care can address such limitations. Evidence exists that patients and providers find the use of computer-based screening acceptable and feasible for inquiring about sensitive issues, including prenatal [53] and postnatal intimate partner violence [54] and mental health [55,56]. It is also well-suited for busy clinical settings in that it offers consistency, is resource-sparing, can be tailored to meet the needs of patients, can be used with audio/video for low literacy, easily provides a real-time summary for patients/providers [56,57], achieves similar rates of disclosure to written- or interview-based screening, and is preferred by patients due to its perceived anonymity [56,58,59].…”
Section: Introductionmentioning
confidence: 99%